2016
DOI: 10.1186/s40545-016-0092-4
|View full text |Cite
|
Sign up to set email alerts
|

The choice between a ritonavir-boosted protease inhibitor- and a non-nucleoside reverse transcriptase inhibitor-based regimen for initiation of antiretroviral treatment – results from an observational study in Germany

Abstract: BackgroundThis study aims at identifying predictors of the treatment decision of German physicians with regard to a non-nucleoside reverse transcriptase inhibitor (NNRTI) or a ritonavir-boosted protease inhibitor (PI/r) -based initial treatment regimen.MethodsThe study is based on a sub analysis of a nation-wide multi-centre, non-interventional, prospective cohort study. 133 patients were identified, who received antiretroviral first-line therapy. By means of a logistic regression, factors that determine the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Since its initial approval in 2006, substantial clinical trial data and clinical experience with darunavir have accumulated, demonstrating the potent and durable virologic response, high genetic barrier to resistance, and favorable safety profile in ART-naive, HIV-1-infected patients [ 4 , 5 ]. A substantial proportion of newly diagnosed patients in the United States and Europe are treated with a boosted protease inhibitor [ 6 , 7 ], and darunavir is the recommended protease inhibitor in treatment guidelines [ 8 – 10 ]. United States guidelines recommend two nucleoside or nucleotide analogue reverse transcriptase inhibitors (NRTIs) combined with an integrase strand transfer inhibitor (INSTI), or in certain clinical situations boosted darunavir 800 mg once daily or a nonnucleoside reverse transcriptase inhibitor (NNRTI) [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since its initial approval in 2006, substantial clinical trial data and clinical experience with darunavir have accumulated, demonstrating the potent and durable virologic response, high genetic barrier to resistance, and favorable safety profile in ART-naive, HIV-1-infected patients [ 4 , 5 ]. A substantial proportion of newly diagnosed patients in the United States and Europe are treated with a boosted protease inhibitor [ 6 , 7 ], and darunavir is the recommended protease inhibitor in treatment guidelines [ 8 – 10 ]. United States guidelines recommend two nucleoside or nucleotide analogue reverse transcriptase inhibitors (NRTIs) combined with an integrase strand transfer inhibitor (INSTI), or in certain clinical situations boosted darunavir 800 mg once daily or a nonnucleoside reverse transcriptase inhibitor (NNRTI) [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…An administrative database analysis of approximately four million beneficiaries showed that German physicians use this flexibility and are more likely to prescribe patients who are in a more advanced disease state (CDC class C) with a PI/r-based regimen than with an NNRTI-based regimen (Mahlich et al, 2015). The same result was obtained in another observational study in Germany (Mahlich et al, 2016).…”
Section: Discussionmentioning
confidence: 59%
“…5 PI combined with two NRTIs in patients initiating ART is standard in certain regions like Germany. 6 However, this patient started ART in Namibia before the scale up of ART in Sub-Saharan Africa. She has commenced ART with dual therapy, including a PI and an NNRTI.…”
Section: Discussionmentioning
confidence: 94%